EU Mapping 2017: Systematic overview on economic and financial legislation - Katja Langenbucher; Tobias H. Tröger; Lara L. Milione; Andreas Roth (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
This study provides a graphic overview on core legislation in the area of economic and financial services. The presentation essentially covers the areas within the responsibility of the Economic and Monetary Affairs Committee (ECON); hence it starts with core ECON areas but also displays neighbouring areas of other Committees' competences which are closely connected to and impacting on ECON's work. It shows legislation in force, proposals and other relevant provisions on banking, securities markets and investment firms, market infrastructure, insurance and occupational pensions, payment services, consumer protection in financial services, the European System of Financial Supervision, European Monetary Union, euro bills and coins and statistics, competition, taxation, commerce and company law, accounting and auditing. Moreover, it notes selected provisions that might become relevant in the upcoming Article 50 TEU negotiations.
urn:nbn:de:hebis:30:3-438858
Keywords: 330; EU economic and financial services legislation